INCREASING WORK PRODUCTIVITY THROUGH ORGANIZATIONAL CULTURE, VISIONARY LEADERSHIP, AND ACHIEVEMENT MOTIVATION - Rifa Ariani; Soewarto Hardhienata; M. Entang (JF Publisher, 2023)
Productivity is a crucial factor in maintaining and improving the quality of education in schools. Good quality education is a measurement for the success of teacher work productivity. In addition, teacher work productivity is affected by organizational culture, achievement motivation, and visionary leadership. Therefore, the objective of this research is to find strategies on ways to increase teacher work productivity by examining the direct and indirect effects of the variables that have been mentioned. This research used survey method in quantitative approach with path analysis technique and STOREM. The sampling technique used is random sampling technique. Respondents involved in the research were 150 out of a total of 238 private high school teachers. The result of the research indicated that there is a positive and significant direct effect: (1) visionary leadership on teacher work productivity (βy1=0.290; α<0.01); (2) organizational culture on teacher work productivity (βy2=0.230; α<0.01); (3)achievement motivation on teacher work productivity (βy3=0.325; α<0.01); (4) visionary leadership on achievement motivation (β31=0.284; α<0.01). Achievement motivation variables do not function effectively as mediating the effect of visionary leadership on work productivity, and function effectively as a mediator of the effect of organizational culture on work productivity. The strategies to improve teacher innovation can be implemented by strengthening the variables of visionary leadership, organizational culture, and achievement motivation. On the other hand, strategies to improve teacher work productivity can be implemented by improving indicators that are still weak, such as strong desire, mission formulation, lesson planning, and student direction.